Long-term real world clinical outcomes of macitentan therapy in chronic thromboembolic pulmonary hypertension. (June 2020) - van Thor, M.C.J.; ten Klooster, L.; Snijder, R.J.; Mager, J.J.; Post, M.C.
Abstract: Background: Macitentan treatment for chronic thromboembolic pulmonary hypertension (CTEPH) in the routine clinical setting is increasing. However, 'real world' macitentan experience is scarce and is needed to differentiate from controlled clinical trial settings. Objective: We describe our outcomes and clinical 'real world' experience of macitentan mono- and combination therapy with riociguat or sildenafil in CTEPH. Methods: We included all consecutive CTEPH patients, either non-operated or with residual PH after pulmonary endarterectomy (PEA), treated with macitentan in the St. Antonius hospital in Nieuwegein, the Netherlands, between 01-2014 and 11-2019. We describe clinical outcomes and adverse events (AEs) until 2 years after macitentan initiation. Results: In total 73 CTEPH patients on macitentan were included, of which 18 patients were clinically inoperable (n = 7 declined PEA, n = 11 nonacceptable risk-benefit) and 55 had technically inoperable CTEPH (n = 48)/residual PH (n = 7). Clinically inoperable patients (mean age 72.4 ± 10.2 years, 61% female, 28% macitentan monotherapy, observation period 2.0 (1.9–2.0) years) had a survival of 100% and clinical worsening (CW)-free survival of 88% at 2-year follow-up respectively, with a significant increased 6-min walking distance (6MWD). Technically inoperable/residual PH patients (mean age 62.1 ± 14.1 years, 60% female, 27% macitentan monotherapy, observation period 2.0 (1.0–2.0) years) had a 2-year survival and CW-free survival of 86% and 68% respectively, with significant improved 6MWD and NT-proBNP. Nonsevere AEs were reported in 30% of all patients. Conclusion: Macitentan mono- and combination therapy in non-operated CTEPH and residual PH is safe and improves clinical outcomes till 2-year follow-up. Highlights: Technical inoperable/residual CTEPH patients treated with macitentan therapy have improved clinical outcomes. Clinically inoperable CTEPH patients treated with macitentan mono- or combination therapy have improved exercise tolerance. Macitentan therapy is safe; without major adverse events.